HUMANITIES IN THE AGE OF ALGORITHMS : A mixed-methods study on the futures of Akava Special Branches in 2036 - Hario, Pasi (My University, 2021)
This master’s thesis in Futures Studies is connected to an assignment from trade union Aka-va Special Branches (AE) to create futures images and to ideate new services for the union in 2036. The research question is the following: How did the mixed-methods foresight process conducted online serve the creation of futures images and new services for Akava Special Branches in 2036? The images and service ideas were cocreated in a mixed-methods foresight process combining elements from Futures Studies and Service Design. The process followed the framework of a participatory futures workshop and was divided into pre-workshop, work-shop, and post-workshop phases. Other methodological tools used were futures window, PESTEL-chart, Dator’s futures archetypes, survey, and futures image. In addition, mood-boards and storyboards, typical Service Design tools, were used to refine the futures images. The end-products of the process were four futures images (consisting of a narrative, a moodboard, and a storyboard) and seven new service ideas. The images were evaluated by the participants in terms of probability and preferability, and the new service ideas in terms of facility to execute and preferability. The workshops were organised with AE’s stakeholders and took place completely online. The online environment promoted accessibility and resulted with heterogenous groups and a representative sample of the intended focus groups. The MIRO platform enabled cocreation but required a tutorial and basic IT-skills to run smoothly. However, facilitating more than one group with MIRO and Microsoft Teams was challenging. Not being physically present at the same place also hindered the communication between the participants. PESTEL-chart worked as a cradle for the pre-assignment and then as a tool for shared understanding in the workshop phase. It also fed driving forces to Dator’s chart of archetypes. Focusing on the Finnish labour market, AE’s organisation and member profile throughout the workshops ensured the micro and macro perspectives in the futures images. The moodboards and storyboards emphasised the communicative value of the images. Evaluation of the images and service ideas after the actual workshops brought an additional layer of validation to the process. The mixed-methods foresight process could be applied to creating futures for any labour union and, as a modified version, for any generic organisation

Pro-gradu on liitoksissa ammattiliitto Akavan Erityisalojen (AE) toimeksiantoon luoda liitolle tulevaisuuskuvia ja ideoita uusista palveluista vuonna 2036. Tutkielman tutkimuskysymys on: miten verkkopohjainen monimenetelmällinen ennakointiprosessi palveli tulevaisuuksien luomista ja uusien palveluiden ideointia Akavan Erityisaloille vuodelle 2036? Ennakointiprosessissa yhdistyivät tulevaisuudentutkimuksen ja palvelumuotoilun menetelmät. Prosessi noudatteli tulevaisuustyöpajan rakennetta ja oli jaettu esiosioon, varsinaiseen ja jälkiosioon. Muita tulevaisuudentutkimukselle tyypillisiä menetelmällisiä työkaluja olivat tulevaisuusikkuna, PESTEL-taulukko, Jim Datorin tulevaisuusarkkityypit, kyselytutkimus ja tulevaisuuskuvat. Palvelumuotoilun työkaluista tulevaisuuskuvia täydentämään käytettiin tunnelmataulua ja palvelusarjakuvaa. Prosessin lopputuotteet olivat neljä tulevaisuuskuvaa koostuen narratiivista, tunnelma-taulusta ja palvelusarjakuvasta sekä seitsemän uutta palveluideaa. Lisäksi osallistujat arvioivat kuvat todennäköisyyden ja toivottavuuden ja palveluideat toimeenpanon helppouden ja toivottavuuden perusteella. Työpajoihin kutsuttiin Akavan Erityisalojen sidosryhmiä ja ne järjestettiin kokonaan verkossa. Verkkoympäristö helpotti osallistumista työpajoihin ja edesauttoi edustavan osallistujaotoksen saamista ja heterogeenisten ryhmien muodostamista. MIRO-alustalla oli helppo luoda näyttäviä tehtävänantoja. Alusta mahdollisti yhteiskehittämisen, mutta vaati osallistujilta harjoittelua ja tietoteknisten perustaitojen hallintaa. Fasilitointi MIRO:n ja Microsoft Teamsin välityksellä oli hankalaa, ja ne mahdollistivat keskittymisen vain yhteen ryhmään kerrallaan. Kehollisen läsnäolon puute myös rajoitti osallistujien välistä viestintää. PESTEL-taulukko toimi hyvin ennakkotehtävässä ja yhteisen ymmärryksen luomiseksi varsinaisen työpajan alussa. Se myös syötti hyvin muutosilmiöitä Datorin tulevaisuuden arkkityyppien taulukkoon. Saman kolmitasoisen katsantotavan säilyttäminen (Suomen työmarkkinajärjestelmä, AE:n organisaatio ja jäsentaso) prosessin eri vaiheissa toi johdonmukaisuutta tulevaisuuskuviin. Tunnelmataulut ja palvelusarjakuvat voimistivat kuvien viestejä. Tulevaisuuskuvien ja palveluideoiden arvottaminen varsinaisten työpajojen jälkeen toi prosessiin lisää uskottavuutta. Monimenetelmällinen metodi olisi sovellettavissa muidenkin ammattiliittojen ja muutoksin toistenkin organisaatioiden tulevaisuuksien rakentamiseen.
Keywords: Labour Unions, Mixed-methods, Futures Images, Foresight, Design Thinking